Revisiting the Role of Exosomes in Colorectal Cancer: Where Are We Now? - Mannavola, Francesco; Salerno, Tina; Passarelli, Anna; Tucci, Marco; Internò, Valeria; Silvestris, Francesco (Frontiers in Oncology, 2019)
Exosomes (Exos) are nano-sized extracellular vesicles constitutively released by both prokaryotic and eukaryotic cells. Their role as inter-cellular messengers involved in both physiological and pathological processes has overwhelmingly come to light in the last decade, and their contribution to cancerogenesis and tumor metastasis is under intensive investigation. Here we review the most recent information concerning Exos in colorectal cancer (CRC) and focus on their effects on tumor microenvironment and immune system as well as unravel their role in formation of the pre-metastatic niche and drug resistance. Such a recent knowledge on Exos depicts their potential translations into the clinical arena, either as alternative tool of “liquid biopsy” or novel therapeutic approaches for CRC. However, due to the limited data available from clinical trials, they need further validations before addressing their putative application in oncology.